Effectiveness of Gamification Problem Based Learning on the Topic of Physical and Chemicsl Change on the Improvement of Student Results of MTs Nurul Islam - Istiqomah, Laili Nur; Maiyanti, Aziza Anggi; Wulandari, Ratna Wahyu; Permana, Niki Dian (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
This study aims to determine the effectiveness of the use of Problem-based learning (PBL) model based on wordwall on the topic of physical and chemical changes to improve the learning outcomes of students of class VII B MTs Nurul Islam. Learners are able to analyze problems that occur in everyday events, because science is side by side with surrounding life. Through PBL students can hone and improve critical thinking skills. The use of wordwall as a learning media in this study makes students more active in learning. Learning in the classroom becomes interactive and the interaction between teachers and students is well developed. Data in this study were obtained from pre-test and post-test scores. This research uses a quantitative approach method using paired t-test and N-gain test. The paired t-test sample test was used to determine any changes in the implementation of research using the wordwall-based PBL learning model. To determine the effectiveness of the learning model, the N-gain test was used. From the results of the paired t-test analysis, it is known that the Sig. (2-tailed) of 0.000 which is smaller than the significance level of 0.05. These results indicate a change in the form of an increase in learning outcomes. It can be concluded that this research is in accordance with the formulation of the hypothesis. The N-gain test was 59.09% and categorized as quite effective. So the use of problem-based learning method is considered effective in this study.